2004
DOI: 10.1161/01.cir.0000136812.90177.94
|View full text |Cite
|
Sign up to set email alerts
|

Sirolimus in De Novo Heart Transplant Recipients Reduces Acute Rejection and Prevents Coronary Artery Disease at 2 Years

Abstract: Background-Sirolimus reduces acute rejection in renal transplant recipients and prevents vasculopathy in nonhuman primates and in-stent restenosis in humans. Its effects on rejection and transplant vasculopathy in human heart transplant recipients are unknown. Methods and Results-In a randomized, open-label study, sirolimus was compared with azathioprine in combination with cyclosporine and steroids administered from the time of cardiac transplantation. We report 6-month rejection rates (primary end point), 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
260
3
8

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 424 publications
(276 citation statements)
references
References 22 publications
5
260
3
8
Order By: Relevance
“…We speculate that this effect of MPA was caused by depletion of cellular GTP content, which was the likely cause for subsequent attenuation of Rac1 activity. Although mTOR inhibitors, such as rapamycin or everolimus, have been observed to have beneficial effects on CAV in clinical settings as well, 42,43 we did not observe an effect of rapamycin on endothelial O 2 Ϫ release in vitro.…”
Section: Krötz Et Al Mpa Inhibits Endothelial Nad(p)h Oxidase 205contrasting
confidence: 69%
“…We speculate that this effect of MPA was caused by depletion of cellular GTP content, which was the likely cause for subsequent attenuation of Rac1 activity. Although mTOR inhibitors, such as rapamycin or everolimus, have been observed to have beneficial effects on CAV in clinical settings as well, 42,43 we did not observe an effect of rapamycin on endothelial O 2 Ϫ release in vitro.…”
Section: Krötz Et Al Mpa Inhibits Endothelial Nad(p)h Oxidase 205contrasting
confidence: 69%
“…[19][20][21][22] A variety of studies investigating coronary artery disease in heart transplant patients, who have baseline endothelial dysfunction, have shown that antiproliferatives such as sirolimus attenuate the rate of atherosclerotic progression. 29,30 In addition, paclitaxel is a well-known immunomodulatory agent and has also been associated with atherosclerotic regression in animal models, as well as reduced inflammation in stented porcine arteries. 23,31 Furthermore, given that the product labeling and pharmacokinetic studies in sirolimus-eluting stents describe serum detectability of antiproliferative agents for over 2.5 weeks and an estimated 3 month elution period after implantation (depending on stent type), one would expect these drugs to have long-term effects on the downstream vascular bed.…”
Section: Discussionmentioning
confidence: 99%
“…37,38 In addition, oral administration of cell-cycle inhibitors prevent in-stent restenosis as well atherosclerotic progression in heart transplant patients, suggesting that serological delivery of drug, without high tunical concentrations, is able to affect stenotic progression. 9,29 Downstream endothelial effects should therefore be expected, in addition to effects on circulating macrophages and lymphocytes that are central to the development and progression of atherosclerotic plaques.…”
Section: Discussionmentioning
confidence: 99%
“…The 48-month follow-up results of this trial demonstrated fewer rejections in the everolimus-treated patients (62). A smaller trial of rapamycin (63) in de novo transplant patients also showed fewer rejection episodes and less coronary allograft vasculopathy. To date, none of the TOR inhibitor trials in heart transplantation have demonstrated increased survival.…”
Section: Target Of Rapamycin Inhibitors (Proliferation Signal Inhibitmentioning
confidence: 69%
“…Some data suggest that a tacrolimus-based immunosuppressive regimen is associated with less coronary intimal thickening than with a cyclosporine-based regimen (84). Newer immunosuppressive agents, including sirolimus and everolimus (85)(86)(87)(88)(89), have shown some early promise in reducing intimal thickening, but their routine use for this purpose requires additional study.…”
Section: Acadmentioning
confidence: 99%